2017
DOI: 10.1080/09537104.2017.1327653
|View full text |Cite
|
Sign up to set email alerts
|

Do methodological differences account for the current controversy on tissue factor expression in platelets?

Abstract: Tissue factor (TF), the key activator of the blood coagulation cascade and of thrombus formation, is also expressed by circulating human platelets. Despite the documented in-depth characterization of platelet TF carried out in the past 15 years, some authors still fail to identify TF in platelets, especially when assessment in platelet-rich plasma (PRP) or washed platelets is carried out. This study aims to extend the characterization of the subset of TF-positive platelets in PRP from healthy subjects and to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…In a recent study showing the presence of substantial amounts of TF in both resting and activated platelets, the authors discuss the controversy around TF expression in platelets due to methodological differences in platelet isolation [32]. The authors argue that only large platelets express functionally active TF antigen, whereas TF activity in small platelets is quenched by TFPI and therefore undetectable.…”
Section: Platelet Preparationmentioning
confidence: 99%
“…In a recent study showing the presence of substantial amounts of TF in both resting and activated platelets, the authors discuss the controversy around TF expression in platelets due to methodological differences in platelet isolation [32]. The authors argue that only large platelets express functionally active TF antigen, whereas TF activity in small platelets is quenched by TFPI and therefore undetectable.…”
Section: Platelet Preparationmentioning
confidence: 99%
“…Brambilla et al found that large platelets express not only significantly higher amounts of tissue factor and tissue factor mRNA compared to small platelets. Large platelets also expose functionally active tissue factor on their cell membranes whereas the activity of tissue factor in small platelets is almost completely quenched by tissue factor pathway inhibitor ( 48 ). These results extent previous findings showing that platelets translate tissue factor ( 52 ) and point toward specific roles of large and small platelets in hemostasis.…”
Section: Size As a Platelet Characteristicmentioning
confidence: 99%
“…Since asTF and flTF serve important and often distinct roles in various biological processes, it is appropriate to study them separately. However, as shown in Table III (15–52), total TF, including asTF and flTF, or flTF alone, has been investigated in studies over the last decade. Few studies have been conducted that have detected asTF and flTF levels separately, according to the primer sequences that have been designed.…”
Section: Discussionmentioning
confidence: 99%